(untitled) (Research, Society and Development, 2020)
This article aims to understand how the governance structure avoids the entrepreneurial skills of Information Technology (IT) in Bahia and is able to influence certain characteristics of public policy in support of non-state productive explorations. As a way to confirm the objective, the proposal is followed by the following steps: i) Characterization of the governance structures of companies that did not start from IT in Bahia; ii) Review of bibliography and public policy documents that reveal or encourage any governance structure; iii) Analyze the influence of the governance structure of two IT entrepreneurs on the characteristics of the support provided by public policies. In search of theoretical support from the Nova Institutional Economics (NEI), specifically in Transaction Cost Economics (ECT), we studied Oliver Williamson (1985, 1990, 1996). Through bibliographic, documentary research and analysis of questionnaires it was possible to arrive at the expected results. As a result, it is possible to affirm that Bahian public policy stimulated, in particular, transactions developed through contracts (hybrids) and price mechanisms (market). It was concluded that the governance structure of IT entrepreneurs was able to stimulate public policy to support productive arrangements in Bahia.